Selling intimacy online: The multi-modal discursive techniques of China's wanghong. (June 2022) - Sandel, Todd L.; Wang, Yusa
Abstract: The development and spread of the internet and social media technologies across China have provided people with alternative pathways for achieving celebrity status and wealth. Such persons, known as wanghong (internet celebrities), can achieve fame by promoting themselves and their online content on a variety of monetised platforms, giving rise to what is called a ' wanghong economy'. Using a social semiotic multimodal approach, this study examines the techniques of wanghong, and the affordances of the digital platforms used to communicate celebrity-fan interaction. In particular, we study three wanghong who construct a distinct online persona on separate apps, Weibo, Douyin, and Bilibili, as they sell perceived intimacy and interaction. This study demonstrates methods for studying Chinese social media platforms.